Advanced computer support for method engineering : implementation of CAME environment in MetaEdit+ - Rossi, Matti (1998)
In today's fast pace of the evolution of software systems and software development practices only customizable CASE tools are flexible enough to change, according to user needs. Customizable CASE tool environments are emerging from laboratories into everyday use. As these tools become more powerful, their configuration for a given task or project becomes harder. At the same time, the number of users grows. To overcome the tool configuration problem, method engineers need computerized tools to assist them. A natural tool for the CASE tool developers is of course a customized CASE toolset, which can be configured for method engineering, i.e. a Computer Aided Method Engineering (CAME) environment. In the thesis we present the development and design rationale of one such tool, called MetaEdit+. The MetaEdit+ tool provides an easy to use method development toolset within the CASE environment. The main contribution of this thesis is the development of an integrated method engineering environment within MetaEdit+, a framework for evaluating CAME tools and a set of metrics for analyzing the developed methods. The thesis also develops a model and a set of tools for reusing method components while developing new methods. The thesis follows a constructive research paradigm. A set of tools and methods for CAME has been designed. The tools have been implemented and tested by developing new methods for MetaEdit+ with them.